Impact on cardiovascular events of increasing high density lipoprotein cholesterol with and without lipid lowering drugs - Wei, L (BMJ Group, 2006)
OBJECTIVE: To estimate the impact on cardiovascular events of changes in high density lipoprotein (HDL) adjusted for changes in total cholesterol. DESIGN: Cohort study based on a record linkage database. SETTING: Community study in Tayside, Scotland, UK. PATIENTS: 18 815 patients were identified for the study between 1989 and 2001. MAIN OUTCOME MEASURES: Cardiovascular events. RESULTS: 5510 patients taking lipid lowering treatment who had not been hospitalised previously for cardiovascular disease had 314 cardiovascular events recorded (9407 person years of follow up). Patients whose HDL rose by > 20% were less likely to have an event (23.5/1000 person years, 95% confidence interval (CI) 17.3 to 29.6) compared with patients whose HDL did not rise (42.6/1000 person years, 95% CI 35.5 to 49.7, adjusted relative risk 0.60, 95% CI 0.44 to 0.83). HDL change and cardiovascular outcome were not significantly associated among patients who had been hospitalised previously for cardiovascular disease or among patients who were not taking lipid lowering drugs. CONCLUSION: In this study a rise in HDL independently predicted reduced cardiovascular risk in patients taking lipid lowering treatment who had not been hospitalised previously for cardiovascular disease.